2017
DOI: 10.26905/jmdk.v5i2.1355
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH BRAND EXPERIENCE TERHADAP BRAND SATISFACTION, BRAND TRUST DAN BRAND LOYALTY (Studi Pada Konsumen Make-Up Brand Impor di Surabaya)

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
3
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 2 publications
3
7
3
11
Order By: Relevance
“…The results of this study support the findings of a study conducted by Pranadata et al (2017) which proves that brand experience has no significant effect on brand loyalty. However, the findings in this study are not in line with the findings of research conducted by Pertiwi et al (2017) wherein the findings it was found that brand experience has a significant influence on brand loyalty.…”
Section: The Influence Of Brand Experience On Brand Loyaltycontrasting
confidence: 99%
See 2 more Smart Citations
“…The results of this study support the findings of a study conducted by Pranadata et al (2017) which proves that brand experience has no significant effect on brand loyalty. However, the findings in this study are not in line with the findings of research conducted by Pertiwi et al (2017) wherein the findings it was found that brand experience has a significant influence on brand loyalty.…”
Section: The Influence Of Brand Experience On Brand Loyaltycontrasting
confidence: 99%
“…The findings in this study are the same as the results of research conducted by Chinomona (2013) which proves that there is a significant influence between brand experience and brand trust. Likewise, the results of research by Pertiwi et al (2017) prove that brand experience has a role in increasing brand trust.…”
Section: The Effect Of Brand Experience On Brand Trustmentioning
confidence: 88%
See 1 more Smart Citation
“…The results in this research support the findings of Pertiwi, Djawahir, and Andarwati (2017) who proved that there are direct significant influences in brand experience toward brand loyalty.…”
Section: Brand Experience Influences Toward Brand Loyaltysupporting
confidence: 89%
“…Results of research by Pertiwi et al (2017); and Putra (2017) show that satisfaction becomes the mediating variable of various independent variables such as experience and image of trust. This is also supported by several findings that satisfaction can be a mediating variable as reviewed by Utama (2017), Papadimitriou et al (2015), Wang et al 2009, Silvestri et al (2017), and Suryaningsih and Sumani (2018).…”
Section: The Tourist Experience and Destination Image On Trust Througmentioning
confidence: 99%